Nutritional trajectories in gastric cancer patients with early oral feeding - Yao, Nan; Chen, Haixia; Han, Leyao; Zhang, Meishan; Yang, Meng; Zhang, Haijun; Wang, Xinglei; Dou, Xinman (Frontiers in Nutrition, 2025)
Background/ObjectivesEvidence on postoperative nutritional dynamics in Chinese gastric cancer (GC) patients is currently limited. This study employs Group-Based Trajectory Modeling (GBTM) to identify Prognostic Nutritional Index (PNI) trajectory patterns and their factors among GC patients under early oral feeding (EOF) management.MethodsThis retrospective study analyzed 124 GC patients undergoing total gastrectomy (2019–2024). PNI trajectories were identified using GBTM, and their associated factors were analyzed via multinomial logistic regression.ResultsThree distinct trajectories emerged: “High nutritional status” (41.9%), “Rapidly declining” (7.3%), and “Decline-Recovery” (50.8%). Compared with the high nutritional status (49.99 ± 4.50), the baseline PNI of the decline-recovery group was lower (44.34 ± 3.57). High Morse Fall Scale (MFS) score (β = 0.092, p = 0.010), low activities of daily living (ADL) (β = −0.655, p = 0.009), AJCC Cancer Stage (β = 2.238, p = 0.002) and vascular and nerve invasion (β = 3.540, p < 0.001) influence unfavorable trajectories.ConclusionPostoperative nutritional trajectories in GC patients managed with EOF are different. Functional impairment (e.g., low ADL, high MFS) and advanced pathological conditions were key determinants of unfavorable nutritional trajectories highlighting the need for targeted monitoring and individualized nutritional interventions for high-risk sub-groups.